Taxes, Wage Capitalization and the Ability of States to Redistribute Income - Seth H. Giertz; Rasoul Ramezani (Global Labor Organization (GLO), 2018)
Local and state governments attempt to lessen after-tax income inequality via progressive taxation. Migration responses of capital and labor undermine such attempts. Location theory predicts that cross-state migration will continue until the redistributive effects from taxation are fully capitalized into gross wages leaving after-tax wages unchanged. Empirical evidence has not reached a consensus on this issue. At one extreme, Feldstein and Wrobel (1998) report evidence of full tax capitalization for US states. At the other extreme, Leigh (2008) reports very little to no wage capitalization. We revisit this question by creating a pseudo panel from CPS data spanning years 1997 to 2015. Our “best” estimate is that pre-tax wages adjust in response to redistributive state and local taxes, negating roughly 50 percent of effect compared to counterfactual with no behavioral responses.
Keywords: H20; H71; H77; 330; Fiscal federalism; Redistribution; State taxation; Tax capitalization; Progressivity; Migration